2007
DOI: 10.1158/1078-0432.ccr-06-2468
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between Arsenic Trioxide and Heat Shock Protein 90 Inhibitors on Signal Transducer and Activator of Transcription Protein 3 Activity—Pharmacodynamic Drug-Drug Interaction Modeling

Abstract: Purpose: Constitutive signal transducer and activator of transcription 3 (STAT3) activity, observed in f50% of acute myelogenous leukemia cases and associated with adverse treatment outcome, is down-regulated by arsenic trioxide (ATO). Heat shock protein (HSP) 90 is a molecular chaperone involved in signal transduction pathways. We hypothesized that HSP90 inhibitors will potentiate ATO effect on constitutive STAT3 activity and cell killing. One concern was that the effect of ATO and HSP90 inhibitors will resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Previous studies demonstrated that sodium arsenite inhibits interleukin-6-dependent tyrosine phosphorylation of STAT3 in HepG2 cells via direct suppression of the tyrosine kinase JAK1 (41). Other studies have shown that As 2 O 3 suppresses activation of STAT1, STAT3, and STAT5 in AML cells and inhibits activation of JAK1 and JAK2, which phosphorylate STATs (42), whereas there is also evidence for a synergism between As 2 O 3 and Hsp90 inhibitors in STAT3 activity (43).…”
Section: Mechanisms Of Arsenic-induced Cell Deathmentioning
confidence: 99%
“…Previous studies demonstrated that sodium arsenite inhibits interleukin-6-dependent tyrosine phosphorylation of STAT3 in HepG2 cells via direct suppression of the tyrosine kinase JAK1 (41). Other studies have shown that As 2 O 3 suppresses activation of STAT1, STAT3, and STAT5 in AML cells and inhibits activation of JAK1 and JAK2, which phosphorylate STATs (42), whereas there is also evidence for a synergism between As 2 O 3 and Hsp90 inhibitors in STAT3 activity (43).…”
Section: Mechanisms Of Arsenic-induced Cell Deathmentioning
confidence: 99%
“…We have shown that arsenic trioxide (ATO) down-regulates constitutive STAT3 activity in AML cells within 6 h, without affecting cell survival until 48 h [2]. Since heat shock protein (HSP) 90 is implicated in maintaining the conformation, stability and function of key proteins involved in signal transduction pathways, we demonstrated that the different HSP90 inhibitors [geldanamycin, 17-allylamino-17-demethoxygeldanamycin (17-AAG), and 17-(dimethyl-aminoethylamino)-17-demethoxygeldanamycin (NSC 707545, 17-DMAG)] augment ATO’s down-regulating effect on constitutive STAT3 (P-STAT3) [3]. Since 17-AAG has poor solubility, the water soluble derivative, 17-DMAG, which is more biologically available, was tested in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction model is not limited to mass-law drug–receptor binding equations, but provides estimates of how much each drug contributes to the interaction after binding to their respective targets. These models were designed to study the effect(s) of down-regulating HSP70 on the known synergistic effect of ATO and 17-DMAG on constitutive STAT3 activity [3]. We therefore incorporated data from our previous study [3] into the current model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenite can induce HSPs expression in a variety of cells 14,15 . HSPs are molecular chaperones which help protein folding and transportation 16,17 .…”
mentioning
confidence: 99%